Sorbet Made from Moringa Leaves and Red Guava as an Alternative for the Management of Iron Deficiency Anemia in Adolescent Girls - Arviyani, Tiffany Nisa; Afifah, Diana Nur; Noer, Etika Ratna; Rahfiludin, M. Zen; Mahati, Endang (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2022)
Moringa leaves (Moringa oleifera) contain high iron (Fe) but low bioavailability of Fe because it contains calcium and tannins. Vitamin C in red guava fruit (Psidium guajava) can increase Fe absorption. Sorbet made from red guava and Moringa leaves can be an alternative to overcome iron deficiency anemia in adolescent girls. This study aims to analyze the level of acceptance, levels of Fe, Ca, vitamin C, and tannins, as well as the bioavailability of Fe sorbet made from red guava and Moringa leaves. Sorbet consists of 5 formulas including, F1 (strawberry sorbet), F2 (red guava sorbet), F3 (Moringa leaf sorbet), F4 (red guava sorbet + 18% Moringa leaves), and F5 (red guava sorbet + 22% Moringa leaves). Acceptance level was tested with the hedonic method (appearance, smell, taste, and texture) and statistically analyzed using Friedman and Wilcoxon test. The Fe and Ca were analyzed using X-Ray Fluorescence (XRF) method, vitamin C and tannins were analyzed using High-Performance Liquid Chromatography (HPLC) and spectrophotometry methods. Fe bioavailability test was performed using the inverted bowel bag method. The level of preference for each attribute was significantly different (p < 0.05). The level of preference chosen was F2. The mean levels of Fe, Ca, vitamin C, and tannins in F4 were 0.95 ± 0.14, 5.91 ± 0.73, 26.29 ± 0.13, and 135.65 ± 0.91 mg/100 g. The mean levels of Fe, Ca, vitamin C, and tannins in F5 were 0.21 ± 0.29, 6.03 ± 0.67, 46.72 ± 0.69, and 87.76 ± 0.40 mg/100 g. The highest Fe bioavailability was F5 while the lowest was F3. The best formula based on the parameters of preference, Fe, Ca, vitamin C, and tannin levels, as well as Fe bioavailability, was sorbet F5.